PENGARUH MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN PENAJAM PASER UTARA - Adilah, Ade Mayang; Yusuf, Tamzil (Fakultas Ekonomi Universitas Balikpapan, 2024)
This study aims to determine the effect of motivation, compensation and work environment on employee satisfaction of the Public Works and Spatial Planning Office. The sampling technique in this study was purposive sampling with a sample size of 83 employees of the Public Works and Spatial Planning Office. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS 3 in processing data. The results of this study indicate that the motivation variable affects the job satisfaction of employees of the Public Works and Spatial Planning Office. The compensation variable affects the job satisfaction of employees of the Public Works and Spatial Planning Office. Work environment variables affect job satisfaction of employees of the Public Works and Spatial Planning Office.